Implementasi Program Makan Bergizi Gratis Dalam Pengurangan Stunting: Studi Literatur Pemerintahan Kabupaten Kupang - Glen Gerardus Mayela Awe; Yohana Krisona; Ave Regina Chandra Kirana; Maimuna Faizah Rahma Atulolon; Agnesia Fifin Kontesa; Fadil Mas’ud (CV. ITTC INDONESIA, 2026)
Stunting is a chronic health problem that affects the quality of human resources and poses a serious challenge in Kupang Regency. The Free Nutritious Meals (MBG) program is a strategic government policy with the potential to support stunting prevention through school-based interventions. This article aims to analyze the implementation of the MBG in addressing stunting in Kupang Regency from the perspective of the local government system and to identify challenges and strategies for strengthening policy governance. The method used is a literature review examining journals related to MBG implementation, good governance, accountability, stakeholder coordination, family education, nutrition interventions, and sanitation. The study’s findings indicate that implementation is influenced by cross-sectoral coordination, fiscal capacity, logistical readiness, and the effectiveness of oversight. Major obstacles include infrastructure limitations, disparities in access to nutritious food, low transparency, and low family nutrition literacy. In conclusion, the success of the MBG requires the integration of transparent, participatory, and sustainable policies.